Gogorevia, a New Monoraphid Diatom Genus for Achnanthes exigua and Allied Taxa (Achnanthidiaceae) Described on the Basis of an Integrated Molecular and Morphological Approach. Issue 6 (27th October 2020) - Kulikovskiy, Maxim; Maltsev, Yevhen; Glushchenko, Anton; Kuznetsova, Irina; Kapustin, Dmitry; Gusev, Evgeniy; Lange‐Bertalot, Horst; Genkal, Sergei; Kociolek, John Patrick
Abstract : A new diatom genus, Gogorevia, is described on the basis of an integrated molecular and morphological investigation. Two species are described from Vietnam: the generitype, G. rinatii sp. nov., and G. ovalis sp. nov. These species share many morphological features with Achnanthes exigua and allied taxa that were previously transferred to the genera Achnanthidium or Lemnicola . Our current molecular investigation shows that Gogorevia is distinct and phylogenetically removed from the above‐mentioned genera. Morphologically, Gogorevia differs from Achnanthidium and Lemnicola by the shape of the valves, possessing uniseriate striae, raphe morphology, and the presence of an evident sternum. The recently described species Lemnicola uniseriata is transferred to Gogorevia on the basis that it possesses the same morphological features and phylogenetic position as other members of the genus.